Analysis of The Influence of Teachers' Teaching Methods and Learning Atmosphere on Students' Understanding Levels at Mi Miftahul Ulum Karangkonang - Fito Muhammad Al Fito Azra (International Journal of Educational Technology Research, 2023)
The purpose of this research is (1) to find out how the teacher's teaching methods influence the level of students' understanding at MI Miftahul Ulum Karangkonang (2) to find out the influence of the learning atmosphere on students' understanding of learning at MI Miftahul Ulum Karangkonang. To obtain the necessary data, the researcher used data collection methods in the form of interviews, observation and documentation, while the analysis method used was a qualitative descriptive method. In this research, the data used were primary and secondary data. The results of this research are (1) the methods used by teachers at MI Miftahul Ulum Karangkonang are effective in increasing students' understanding (2) the learning atmosphere is sufficient to support learning activities coupled with adequate school facilities so as to increase students' understanding of the material. given. Teaching methods and learning atmosphere are two important factors that teachers at MI Miftahul Ulum Karangkonang must pay attention to in order to continue to increase student motivation and interest in learning.